Microstructure, corrosion, and wear resistance of a boron-modified duplex stainless steel produced by laser powder bed fusion - Freitas, Brenda Juliet Martins (2024)
A duplex stainless steels (DSS) containing 0.3 and 0.6 wt.% of boron were produced by laser powder bed fusion (L-PBD) with parameters based on Box-Behnken design. The microstructure was evaluated by XRD, OM, SEM, EBSD, TEM, and ASTAR. Additionally, the alloys were characterized by Vickers microhardness, reciprocating pin-on-plate wear test in sliding mode, and the electrochemical behavior was assessed by cyclic potentiodynamic polarization, electrochemical impedance spectroscopy, and double loop electrochemical potentiokinetic reactivation tests in chloride electrolyte. The results were compared to a pure duplex stainless steel obtained by hot-rolling and by LPBF. Hot-rolled pure DSS presents a dual-phase (α+γ) microstructure with elongated grains along the rolling axis, whereas the as-built LPBF pure DSS exhibits coarsened columnar δ-Fe grains parallel to the building direction. In contrast, boron addition promoted an outstanding grain refinement, resulting in a microstructure non-textured microstructure and composed of refined equiaxed δ-Fe grains with Cr2B nanoborides decorating the grain boundaries. Such excellent grain refinement is ascribed to the segregation of boron and accumulation of a boron-enriched boundary layer ahead of the growing solid-liquid interface during LPBF solidification. Regarding hardness and wear resistance, compared to the commercial hot-rolled DSS, the LPBF-produced pure DSS presented enhanced hardness and wear resistance, which are further increased by boron addition. Moreover, LPBF-produced boron-containing stainless steel revealed high pitting resistance, great repassivation ability, and unsensitized microstructure in 0.6M NaCl solution, being comparable to pure DSS produced by LPBF and by hot-rolling. Therefore, the addition of boron is responsible for the formation of a wear- and corrosion-resistant ultrafine-grained LPBF-produced stainless steel, opening the possibility of applying this material in challenging environments givens its excellent basket of electrochemical and tribological properties.